Comparative Study of Hydrogen Electrooxidation on Gold and Platinum in Solutions Containing Perchlorate Ion - Von Mengershausen, Alicia E. (2014)
The electrooxidation of hydrogen on platinum and gold electrodes is comparatively described in this paper. The reaction is faster on platinum than on the gold surface, because the reactive diffuses inside of the gold metal. This process is complicated with the lift of surface reconstruction of the (100) plane, which allows the fast penetration of the H atoms through the more open surface. The diffusion limiting current is then discontinued and the current falls. On platinum, the current fall occurs simultaneously with the metal oxide formation. It is assumed that the hydrogen helps the adsorbed OH group formation, which is the first step of metal oxidation, and it has been called “incipient hydrous oxide” (IHO). Current begins to fall slowly at the (IHO) potential. At higher potential the current falls abruptly.